2021
DOI: 10.1101/2021.10.27.466138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Locus Coeruleus- dorsal CA1 dopaminergic circuit modulates memory linking

Abstract: SummaryIndividual memories are often linked so that the recall of one triggers the recall of another. For example, contextual memories acquired close in time can be linked, and this is known to depend on temporary increase in excitability that drive the overlap between dorsal CA1 (dCA1) hippocampal ensembles encoding the linked memories. Here, we show that the Locus Coeruleus (LC) cells projecting to dCA1 have a key permissive role in contextual memory linking, without affecting contextual memory formation, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 120 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…In our experiment, exposure to a novel environment caused an increase in LC axon activity but not in VTA DA axon activity, supporting findings that novel experiences induce activity of LC neurons [Takeuchi et al, 2016 ]. The activity of LC neurons in turn increases hippocampal neuron activity [Wagatsuma et al, 2018 ], increases efficacy of Schaffer Colateral synapses [Takeuchi et al, 2016 ], stabilizes place cells across days [Wagatsuma et al, 2018 ] and memory persistence [Wagatsuma et al, 2018, Takeuchi et al, 2016, Chowdhury et al, 2022 through dopamine receptor dependent mechanisms. Importantly, while LC inputs to CA1 have been shown to cause an increase in activity [Wagatsuma et al, 2018, Chowdhury et al, 2022, shape over-representation of novel reward locations [Kaufman et al, 2020 ], and modulate memory linking [Chowdhury et al, 2022 ], they have not been shown to play a role in the formation of contextual memories [Chowdhury et al, 2022 ] or stabilization of place cell maps across days [Wagatsuma et al, 2018 ] in dCA1.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our experiment, exposure to a novel environment caused an increase in LC axon activity but not in VTA DA axon activity, supporting findings that novel experiences induce activity of LC neurons [Takeuchi et al, 2016 ]. The activity of LC neurons in turn increases hippocampal neuron activity [Wagatsuma et al, 2018 ], increases efficacy of Schaffer Colateral synapses [Takeuchi et al, 2016 ], stabilizes place cells across days [Wagatsuma et al, 2018 ] and memory persistence [Wagatsuma et al, 2018, Takeuchi et al, 2016, Chowdhury et al, 2022 through dopamine receptor dependent mechanisms. Importantly, while LC inputs to CA1 have been shown to cause an increase in activity [Wagatsuma et al, 2018, Chowdhury et al, 2022, shape over-representation of novel reward locations [Kaufman et al, 2020 ], and modulate memory linking [Chowdhury et al, 2022 ], they have not been shown to play a role in the formation of contextual memories [Chowdhury et al, 2022 ] or stabilization of place cell maps across days [Wagatsuma et al, 2018 ] in dCA1.…”
Section: Discussionsupporting
confidence: 83%
“…The activity of LC neurons in turn increases hippocampal neuron activity [Wagatsuma et al, 2018 ], increases efficacy of Schaffer Colateral synapses [Takeuchi et al, 2016 ], stabilizes place cells across days [Wagatsuma et al, 2018 ] and memory persistence [Wagatsuma et al, 2018, Takeuchi et al, 2016, Chowdhury et al, 2022 through dopamine receptor dependent mechanisms. Importantly, while LC inputs to CA1 have been shown to cause an increase in activity [Wagatsuma et al, 2018, Chowdhury et al, 2022, shape over-representation of novel reward locations [Kaufman et al, 2020 ], and modulate memory linking [Chowdhury et al, 2022 ], they have not been shown to play a role in the formation of contextual memories [Chowdhury et al, 2022 ] or stabilization of place cell maps across days [Wagatsuma et al, 2018 ] in dCA1. However, it is possible this novelty induced activity in LC inputs to dCA1 impacts the formation of instant place fields observed in novel environments [Sheffield et al, 2017, Dong et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was recently reported that DA released by LC cells projecting to dCA1 have a key permissive role in contextual memory linking (Chowdhury et al, 2021). Moreover, the rule could also accommodate a temporally discontiguous instructive learning signal or a specific supervisory feedback signal.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, time-varying excitability may account for overlapping neural ensembles encoding memories of events that are temporally linked (Sehgal et al ., 2018), namely events spaced by a short temporal delay, as observed in the lateral amygdala (Rashid et al ., 2016), the hippocampal dorsal CA1 (Cai et al ., 2016; Shen et al ., 2022), and the retrosplenial cortex (Sehgal et al ., 2021). Previous theoretical works have described how the dynamics of plasticity-related proteins and excitability can lead to co-allocation of memories at the dendritic level (Kastellakis et al ., 2016; Sehgal et al ., 2021; Chowdhury et al ., 2021). Attractor networks (Amit, 1989) have been previously used to describe the recurrent network properties of overlapping memory engrams (Gastaldi et al ., 2021) but without taking excitability into account.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical works have described how the dynamics of plasticity-related proteins and excitability can lead to co-allocation of memories at the dendritic level (Kastellakis et al, 2016;Sehgal et al, 2021;Chowdhury et al, 2021). Attractor networks (Amit, 1989) have been previously used to describe the recurrent network properties of overlapping memory engrams (Gastaldi et al, 2021) but without taking excitability into account.…”
Section: Introductionmentioning
confidence: 99%